1988
DOI: 10.1111/j.1600-0714.1988.tb01531.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical localization of intermediate filament proteins in calcifying epithelial odontogenic tumors

Abstract: Three calcifying epithelial odontogenic tumors (CEOT) were examined immunohistochemically. The localization of intermediate filaments was characterized through the use of polyclonal anti‐keratin antiserum (TK which detects 41–65 kd keratins), 2 monoclonal keratin antibodies (PKK1 specific for the 44, 46, 52 & 53 kd keratins and KL1, specific for the 55–57 kd keratins) and monoclonal antibodies for vimentin and desmin. The tumor epithelial cells were slightly positive or negative for PKK1 detectable keratins, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
12
0
1

Year Published

1988
1988
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 22 publications
4
12
0
1
Order By: Relevance
“…Consistent with many previous studies reporting the negativity of the amyloid-like material to various different molecular weight cytokeratins (Mori et al 1988;Asano et al 1990;Saku et al 1992;Takata et al 1993;Kumamoto et al 1999Kumamoto et al , 2001Cheng et al 2002;Crivelini et al 2003), the present study found that the amyloid-like deposits did not react to cytokeratins that are present in the antibody clone AE1/AE3. Nevertheless, one study showed that the amyloid deposit is immunoreactive for the cocktail of cytokeratins 1, 5, 6, 8, 13, 16 and pan-cytokeratins AE1/AE3 (Aviel-Ronen et al 2000).…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…Consistent with many previous studies reporting the negativity of the amyloid-like material to various different molecular weight cytokeratins (Mori et al 1988;Asano et al 1990;Saku et al 1992;Takata et al 1993;Kumamoto et al 1999Kumamoto et al , 2001Cheng et al 2002;Crivelini et al 2003), the present study found that the amyloid-like deposits did not react to cytokeratins that are present in the antibody clone AE1/AE3. Nevertheless, one study showed that the amyloid deposit is immunoreactive for the cocktail of cytokeratins 1, 5, 6, 8, 13, 16 and pan-cytokeratins AE1/AE3 (Aviel-Ronen et al 2000).…”
Section: Discussionsupporting
confidence: 94%
“…Many previous studies have shown the immunoreactivity of CEOT-neoplastic cells to many cytokeratins including cytokeratins 14, 19, pan-cytokeratins AE1/ AE3 and a cocktail of cytokeratins 1, 5, 6, 8, 18, 19 (Sauk et al 1985;Mori et al 1988;Asano et al 1990;Saku et al 1992;Takata et al 1993;Aviel-Ronen et al 2000;Kumamoto et al 2001;Crivelini et al 2003). These results indicate the epithelial nature of the CEOT-neoplastic cells.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…In a study examination of CEOT immunohistochemically for localization of intermediate filament proteins, the tumor epithelium cells were slightly positive or negative for (monoclonal keratin bodies) PKKI detectable keratins, but slightly to strong positive for KLI (monoclonal keratin bodies) and TK (polyclonal anti-keratin antibodies), tumor epithelium was slightly positive for vimentin but negative for desmin 32 . Two enamel proteins, amelogenin and enamelin were located in small foci in a case of CEOT when detected immunohistochemically 33 .…”
Section: Ihc (Immunohistochemistry)mentioning
confidence: 99%